Work as an educational principle and the role of intellectuals in the class society - Almeida, Jémerson Quirino de; Castro, Alexandre de (Faculdade de Filosofia e Ciências, 2021)
The dual purpose of this text is to discuss the concept of work as an educational principle and the role of intellectuals in class society. Firstly, we base our reflections on two important theoretical references related to the conception of work: Marx (1998) and Engels (2008), and we turn to Gramsci (1985; 2001; 2010) and its formulation regarding the educational principle. For it was from the marxist-hegelian historical-social analysis that Gramsci formulated his reflection on the concept of work as an educational principle. In this sense, the understanding of the argumentative relationship between these authors is of fundamental importance to establish a relationship between education and intellectuals. The result of these discussions made it possible to approach Edward Said (2005) and allowed some considerations regarding the role of intellectuals in today's class society. In this way, we realize that education for work is a topic of great merit for intellectuals who seek to understand their role in contemporary society.